THE EFFECT OF MULTI-STATION INTERACTIVE TRAINING ON TRANSITION SPEED AND DRIBBLING IN YOUNG FOOTBALL PLAYERS - Dr. Yasser Jaafar Abdullah (Proximus Journal Publishing, 2025)
This study identifies the effect of multi-station interactive training on developing transitional speed and dribbling skills among young football players. The study employed an experimental design with two groups (experimental and control). This approach allows for direct measurement of the training program's impact and comparison of performance between the two groups, while controlling for external factors that might influence the results. The population of the study was purposively selected to include all young football players in Diyala Governorate for the 2023 football season, totaling 176 players. The research sample consisted of 22 players from the Jadida Al-Shatt Club. The experimental group was randomly selected by lottery, comprising 10 players, while the control group also consisted of 10 players, selected using the same method. With the exclusion of (2) goalkeepers for statistical purposes to ensure consistency of technical performance in the tests, and to ensure the validity of the exercises and tests, the pilot study was conducted on (5) players from outside the research sample. This was to assess the suitability of the training, the clarity of the instructions, and to determine the time of each exercise in accordance with the level of the players. The results led to the most important conclusion that interactive multi-station training is an effective way to improve the physical and technical aspects of young players. The most important recommendations were: It is recommended that similar training programs be included in the plans for preparing young players in sports clubs.
Keywords: Interactive multi-station training; transition speed; dribbling